The microbiota and immune-mediated diseases: Opportunities for therapeutic intervention - Mills, Kingston (My University, 2020)
A multitude of diverse microorganisms, termed the microbiota, reside in the gut, respiratory tract, skin, and genital tract of humans and other animals. Recent advances in metagenomic sequencing and bioinformatics have enabled detailed characterization of these vital microbial communities. Studies in animal models have uncovered vital previously unrecognized roles for the microbiota in normal function of the immune responses, and when perturbed, in the pathogenesis of diseases of the gastrointestinal tract and lungs, but also at distant sites in the body including the brain. The composition of gut and respiratory microbiota can influence systemic inflammatory responses that mediate asthma, allergy, inflammatory bowel disease, obesity-related diseases, and neurodevelopmental or neurodegenerative conditions. Experiments in mouse models as well as emerging clinical studies have revealed that therapeutic manipulation of the microbiota, using fecal microbiota transplantation, probiotics, or engineered probiotics represent effective nontoxic approaches for the treatment or prevention of Clostridium difficile infection, allergy, and autoimmune diseases and may enhance the efficacy of certain cancer immunotherapeutics. This review discusses how commensal bacteria can influence immune responses that mediate a range of human diseases and how the microbiota are being targeted to treat these diseases, especially those resistant to pharmacological therapies.
Keywords: cancer immunotherapeutics, microbiota; microbial communities; metagenomic sequencing and bioinformatics; Allergy; Autoimmune disease; Cancer; Neurological disease; cancer immunotherapeutics, microbiota; microbial communities; metagenomic sequencing and bioinformatics